Evaluación de la calidad de suelos con cultivos de zea mays (maíz) en la parroquia rural chacarita del cantón ventanas, provincia los ríos, ecuador - Vera Bravo, María Auxiliadora (2024)
Soil quality is essential for the performance of agriculture; this activity is carried out by farmers who work with techniques that support the development of their production. The use of agrochemicals and the socioeconomic aspect is an influential factor in environmental soil management. The purpose of the study was to evaluate soil quality for corn (Zea Mays) cultivation in the rural parish of Chacarita, Ventanas canton. The research involved a socioeconomic study and the use of agrochemicals through surveys of small farmers in the study area. In addition, laboratory analysis was carried out to evaluate physicochemical parameters. Statistical analysis techniques were also applied using SPSS software and the ArcGIS tool for the spatial distribution of heavy metals. The results revealed that most of the farmers, especially those between 50 and 70 years old, have a primary education, representing 58.21% of the total. These farmers, who are mainly smallholders with limited land, generate incomes of less than $5,000. Physical chemical analysis of the soil indicated a pH less than 5.5 acid, low organic matter content, and high levels of lead (Pb) and zinc (Zn). In addition, the soil was determined to be of moderate quality, classified as class 3. Consequently, a soil remediation proposal was implemented to reduce the levels of heavy metals, highlighting the need for a more sustainable and prudent management of agrochemicals.